Thoracic combined spinal epidural anesthesia for laparoscopic cholecystectomy: A feasibility study - Nandita Mehta; Mohd Reidwan Dar; Shikha Sharma; Kuldeep Singh Mehta (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: The use of regional anesthesia for laparoscopic cholecystectomy has been reserved for patients who are at high-risk under general anesthesia (GA). The aim of this study was to assess whether thoracic combined spinal epidural (CSE) anesthesia is a feasible option for American Society of Anesthesiologists (ASA) physical status I and II patients undergoing elective laparoscopic cholecystectomy. Material and Methods: Thirty ASA physical status I and II patients undergoing elective laparoscopic cholecystectomy received thoracic CSE anesthesia at T9-T10 or T10-T11 interspinous space using the midline approach. Two ml of isobaric levobupivacaine 0.5% with 25 μg of fentanyl was given intrathecally. Results: Surgery was conducted successfully in all except one patient. Thoracic CSE was performed at T9-T10 interspace in 25 patients and T10-T11 interspace in five patients. Paresthesia occurred in two patients (6.6%) transiently on Whitacre needle insertion that disappeared spontaneously. Dural puncture on epidural needle insertion occurred in one patient, and intrathecal placement of epidural catheter occurred in one. Ten patients (33%) complained of shoulder pain. Conversion to GA was done in one patient due to severe shoulder pain and anxiety. Hypotension occurred in 11 patients (36%) and all responded to single dose of mephenteramine 6 mg and fluid bolus. Bradycardia occurred in six patients (20%) which was managed in all with a single dose of atropine. Conclusion: Thoracic CSE anesthesia can be used effectively for ASA I and II patients undergoing laparoscopic cholecystectomy with significant postoperative benefits.